The impact of the National Program of Beekeeping on the evolution of the beekeeping sector - Gabriela Gimbăşanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
It is clear that the National Beekeeping Programme was a true support for Romanian beekeepers, contributing to the development of this branch of agriculture with important sums of money that they could access reflected both in the number of bee colonies and the the quantity of honey valued. Continuing this program is essential for beekeepers because this is a costly occupation that requires a lot of knowledge in beekeeping, and is knownthat the bees are very sensitive.
Keywords: 330; National Beekeeping Programme; bee colonies; honey